Content Creator Searching Mobile-Based Web Application System for GreatWorks Ideas Sdn. Bhd. - Juwani, Nurul Nafisah Nabilah binti Juwani; Suhaila binti Mohd Yasin, (Applied Information Technology And Computer Science, 2024)
In the marketing industry, public relation managers often struggle to find and manage potential content creators for their campaigns. The current process involves using various social media applications and investigating the content creator's suitability, thus making it time-consuming and challenging. To address these issues, a system that manages all content creators is proposed. The system allows public relation managers to easily search, evaluate, and manage them. The system includes a user-friendly interface and search functionality, allowing public relation managers to quickly find suitable content creators based on various criteria. Further, the system allows organizing and managing the content creators’ portfolios and information. The approach is used and guided by basic SDLC methodology. The web application is developed with PHP, HTML, CSS, Javascript, MySQL and Flutter. It is believed that this system will increase the company’s credibility and aid in standing out from competitors.